PENGARUH PEMBERIAN VITAMIN B KOMPLEK TERHADAP PEMULIHAN FISIOLOGI, KONSUMSI PAKAN, DAN BOBOT BADAN KAMBING KACANG MUDA DAN DEWASA PASCA TRANSPORTASI - Apri Fendy Ramadhan; Sularno Dartosukarno; Agung Purnomoadi (Universitas Wahid Hasyim, 2017)
The research aimed to assess the effect of vitamin B complex to the physiological, feed intake, and body weight recovery in Kacang goat after being transported. The materials used were 16 male Kacang goats which were divided into two age groups namely young and mature. The experimental design used in this research was a nested design two phases with two age groups, and Vitamin B complex nested at each age group which was given the feed without (T0) and with vitamin B complex (T1). Parameters observed were physiologic (heart rate, frequency of breathing and body temperature), feed intake and body weight gain. The results during transportation showed that the heart rate of T0 sheep was higher than of T1 (109 vs 96.5 beat/min; P<0.05), but the frequency of breathing and body temperature was not different (P>0.05) as well as physiologically between young and adult goats (P<0.05). The day required for recovery of heart rate, frequency of breathing, body temperature and feed consumption between the treatments were not different (P>0.05) as well as at between young and adult goats (P>0.05). Similar results were found in the day required for recovery of body weight in the T0 and T1, as well as in young and adult goats (P>0.05). The conclusion could be drawn from this study were vitamin B complex could reduce stress levels, but did not affect the day required for physiological recovery, feed intake and body weight in Kacang goats after 7 hours transportation. Keywords: Transportation, stress, Kacang goat, age, vitamin B Complex, recovery.